2013
DOI: 10.1073/pnas.1220847110
|View full text |Cite
|
Sign up to set email alerts
|

CaBP1, a neuronal Ca 2 + sensor protein, inhibits inositol trisphosphate receptors by clamping intersubunit interactions

Abstract: Calcium-binding protein 1 (CaBP1) is a neuron-specific member of the calmodulin superfamily that regulates several Ca 2+ channels, including inositol 1,4,5-trisphosphate receptors (InsP 3 Rs). CaBP1 alone does not affect InsP 3 R activity, but it inhibits InsP 3 -evoked Ca 2+ release by slowing the rate of InsP 3 R opening. The inhibition is enhanced by Ca 2+ binding to both the InsP 3 R and CaBP1. CaBP1 binds via its C lobe to the cytosolic N-terminal region (NT; residues 1-604) of InsP 3 R1. NMR paramagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 49 publications
(83 reference statements)
2
39
0
Order By: Relevance
“…During the past decade, structural information on the IP 3 R protein has been obtained by three major structural techniques: X-ray crystallography [2831], NMR spectroscopy [32,33] and single-particle cryo-EM [19,3440]. However, given the exceptionally large size of the entire IP 3 R channel (~1.2 MDa), only single particle cryo-EM was able to tackle the structure of the full-length tetrameric channel assembly.…”
Section: Brief Retrospective On the Ip3r Structural Studiesmentioning
confidence: 99%
“…During the past decade, structural information on the IP 3 R protein has been obtained by three major structural techniques: X-ray crystallography [2831], NMR spectroscopy [32,33] and single-particle cryo-EM [19,3440]. However, given the exceptionally large size of the entire IP 3 R channel (~1.2 MDa), only single particle cryo-EM was able to tackle the structure of the full-length tetrameric channel assembly.…”
Section: Brief Retrospective On the Ip3r Structural Studiesmentioning
confidence: 99%
“…In aggregate with data demonstrating that Ca 2+ -CaBP1 inhibits InsP 3 -evoked Ca 2+ release (Haynes et al, 2004; Kasri et al, 2004b; Li et al, 2013) a novel regulatory molecular mechanism has been proposed where CaBP1 clamps the intersubunit interactions and thereby inhibits channel opening (Fig. 4C) (Li et al, 2013). …”
Section: Structural Studies Of Insp3rsmentioning
confidence: 77%
“…Importantly, Li et al produced covalently linked tetrameric InsP 3 R1-NT through site-specific cysteine insertions in the intersubunit interface that was modeled in the docking studies and demonstrated that InsP 3 inhibits cross-linked tetrameric InsP 3 R1-NT in a concentration-dependent manner, suggesting that InsP 3 binding closes the clam-like IBC, disrupting these intersubunit interactions and allowing the channel to open (Fig. 4C) (Li et al, 2013). Taken together, these observations indicate that the InsP 3 R1-NT plays a critical role in the allosteric modulation of ion channel conductance through a modification of quaternary arrangement.…”
Section: Structural Studies Of Insp3rsmentioning
confidence: 99%
See 2 more Smart Citations